2010
DOI: 10.1073/pnas.1009427107
|View full text |Cite
|
Sign up to set email alerts
|

Separating mitogenic and metabolic activities of fibroblast growth factor 19 (FGF19)

Abstract: FGF19 and FGF21 are distinctive members of the FGF family that function as endocrine hormones. Their potent effects on normalizing glucose, lipid, and energy homeostasis in disease models have made them an interesting focus of research for combating the growing epidemics of diabetes and obesity. Despite overlapping functions, FGF19 and FGF21 have many discrete effects, the most important being that FGF19 has both metabolic and proliferative effects, whereas FGF21 has only metabolic effects. Here we identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 26 publications
9
107
2
Order By: Relevance
“…BrdU-labeling index of hepatocytes was eight fold higher in the transgenic mice than age-matched wild type mice at 2 to 4 months of age (Nicholes et al, 2002). Furthermore, recombinant FGF19 protein also induced a significant higher BrdU-labeling index after being injected into normal mice (Nicholes et al, 2002;Wu et al, 2010a;Wu et al, 2010b). These results strongly support the notion that FGF19 can induce hepatocellular proliferation which eventually leads to development of HCC.…”
Section: Fgf Pathwaysupporting
confidence: 75%
See 1 more Smart Citation
“…BrdU-labeling index of hepatocytes was eight fold higher in the transgenic mice than age-matched wild type mice at 2 to 4 months of age (Nicholes et al, 2002). Furthermore, recombinant FGF19 protein also induced a significant higher BrdU-labeling index after being injected into normal mice (Nicholes et al, 2002;Wu et al, 2010a;Wu et al, 2010b). These results strongly support the notion that FGF19 can induce hepatocellular proliferation which eventually leads to development of HCC.…”
Section: Fgf Pathwaysupporting
confidence: 75%
“…Strong FGFR4 mRNA was detected in hepatocytes adjacent to central vein by in situ hybridization, and the hepatic dysplasia foci and BrdU labeling from FGF19 transgenic livers are also located around central vein. In addition, activation of FGFR4 alone was sufficient to induce hepatocyte proliferation (Wu et al, 2010a;Wu et al, 2010b) and FGF19 induced hepatocytes proliferation was not observed in FGFR4 knockout mice, confirming the role played by FGFR4 in hepatocarcinogenesis (Wu et al, 2011).…”
Section: Fgf Pathwaymentioning
confidence: 60%
“…Recombinant FGF19, FGF21, and FGF19dCTD proteins used in this study were expressed and purifi ed from Escherichia coli as previously described ( 13,15 ). our previous report demonstrating that activation of FGFR4 alone does not improve glucose parameters ( 15 ).…”
Section: Expression and Purifi Cation Of Recombinant Fgf19 And Fgf21 mentioning
confidence: 99%
“…2B) (30). Furthermore, a recent study, in which N-terminal sequences between FGF19 and FGF21 were swapped to map residues in FGF19 that permit binding of FGF19 to FGFR4, led to the identification of residues 38 -42 at the N terminus of FGF19 as the key determinants of FGF19-FGFR4 specificity (70). This FGF19 N-terminal region corresponds to the FGF1 region that mediates degenerate binding of FGF1 to both alternative splice isoforms of FGFR2 (Fig.…”
Section: Discussionmentioning
confidence: 99%